PERBANDINGAN KETEPATAN KLASIFIKASI MODEL PREDIKSI KEPAILITAN BERBASIS AKRUAL DAN BERBASIS KAS STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Twenty Vivi Kartika; Nur Hidayati; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to determine the comparison between the accrual basis and thecash basis that can be used by a company to detect financial difficulties. Thesampling technique was carried out by purposive sampling method. The data usedin this research is secondary data. Data analysis method used in this research isusing multiple linear regression test, data normality test, classical assumption testwith f test hypothesis testing, determination test, and t test. the results of this studyindicate that accrual-based financial ratios are better able to predict bankruptcythan cash-based financial ratios.Keywords: financial difficulties, bankruptcy, forecast bankruptcy based onaccrual basis, forecast bankruptcy based on cash basis.